Environment and curricular training: a study on curricular environmentalization - Pincerato, Giuliano Mikael Tonelo; Arana, Alba Regina Azevedo; Bertoli, Suzana Chiari (Revista Ensino de Geografia (Recife), 2021)
The objective of the research was to verify the environmental perception and the indicators of curricular environmentalization of the Engineering courses of a university center in Araçatuba-SP. This is an applied research of a qualitative nature using the case study as a method. There was the analysis of the IDPs and PPCs five courses of Engineering (Civil, Mechanical, Electrical, Computer and Mechatronics) where they were raised to the presence of radicals: ambient * SUSTAINABLE * natur *, ecolog *, soc * And Preserve. The results show that the most frequent radical was the soc* followed by the ambient* radical, while the other indicators were present in a smaller number. It is concluded that the coursesstudied have a low environmentalization index.